(untitled) (Kronika Bydgoska, 2016)
Discipline in the highly bureaucratic and militarized Kingdom of Prussia was of key importance. It had a special place in school, constituting a vital factor in shaping student’s personality and building the respect and authority of teacher. This article, using the example of the 19th-century Royal Grammar School of Bydgoszcz, presents interactions between teachers and students in the context of the principles of discipline and punishment system contained in school regulations.